Long-term Survival with 18-Fluorodeoxyglucose Positron Emission Tomography-directed Therapy in Non-small Cell Lung Cancer with Synchronous Solitary Brain Metastasis. Issue 3 (March 2021) - Newman, S.; Bucknell, N.; Bressel, M.; Tran, P.; Campbell, B.A.; David, S.; Haghighi, N.; Hanna, G.G.; Kok, D.; MacManus, M.; Phillips, C.; Plumridge, N.; et al.
Abstract: Aims: At diagnosis, <1% of patients with non-small cell lung cancer (NSCLC) have synchronous solitary brain metastasis (SSBM). In prior cohorts without 18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) staging, definitive treatment to intracranial and intrathoracic disease showed a 5-year overall survival (OS) of 11–21%. We investigated the long-term survival outcomes for patients with SSBM NSCLC, diagnosed in the FDG-PET/CT era and treated definitively with local therapies to both intracranial and intrathoracic sites of disease. Materials and methods: This retrospective study assessed patients staged with FDG-PET/CT who received definitive lung and SSBM treatment from February 1999 to December 2017. A lung-molecular graded prognostic assessment (lung-molGPA) score was assigned for each patient using age, performance status score, and, where carried out, molecular status. Overall survival and progression-free survival (PFS) were calculated using Kaplan–Meier methods. Cox proportional hazard models determined OS and PFS prognostic factors. Results: Forty-nine patients newly diagnosed with NSCLC and SSBM had a median age of 63 years (range 34–76). The median follow-up of all patients was 3.9 years. Thirty-three patients (67%) had ≥T2 disease, 23 (47%) had ≥N2. At 2 years, 45% of first failures were intracranial only (95% confidence interval 30–59). At 3 and 5 years, OS was 45% (95% confidence interval 32–63) and 30% (95% confidence interval 18–51), respectively. In ≥N1 disease, 5-year OS was 34% (95% confidence interval 18–63). The 3- and 5-year PFS was 8% (95% confidence interval 3–22) and 0%, respectively. Higher lung-molGPA was associated with longer OS (hazard ratio 0.26, 95% confidence interval 0.11–0.61, P  = 0.002). Higher lung-molGPA (hazard ratio 0.33, 95% confidence interval 0.15–0.71, P  = 0.005) and lower N-stage (hazard ratio 1.56, 95% confidence interval 1.13–2.15, P  = 0.007) were associated with longer PFS. Conclusions: Definitive treatment of patients with NSCLC and SSBM staged with FDG-PET/CT can result in 5-year survivors, including those with ≥N1 disease. Highlights: Patients in this study had contemporary imaging with brain MRI and whole-body FDG-PET/CT. Appropriate selection of patients presenting with solitary brain metastases for definitive treatment of the lung and brain was associated with a favourable 5-year overall survival. Prolonged overall survival was also noted in those patients with >N1 disease. Highlights the need for future prospective studies to guide the management of patients with oligometastatic NSCLC.